Cluster Control in Oligouranyl Complexes of p-t-Butylcalix[8]arene - Harrowfield, J.; Ogden, Mark; Skelton, B.; White, A. (The Royal Society of Chemistry, 2010)
Formation of uranyl ion complexes of p-t-butylcalix[8]arene by reaction of the calixarene with [UO2(dmso)5]2+ in the presence of various bases leads to the crystallisation of solids with interestingly different stoichiometry, involving both di- and tri-uranate oligomers bound to the calixarene in anionic species. In all, the calixarene hexa-anion is present in a virtually identical conformation, suggesting that conformational preferences of the ligand must be a major factor controlling the form of the bound oxo-metal complex. Hydrogen bonding to the anions does not appear to be prominent even in the presence of protonated amines and this may explain the formation of some remarkable cation/solvent/simple anion clusters found within the lattices.